WOMEN’S ACTIVITY IN STATE AND NON-GOVERNMENT ORGANIZATIONS - Fotima Jumanazarova (Social science and innovation, 2023)
This article analyzes the activities of women and girls in state and non-state organizations and the conditions created for them. Today, in our country, the free activity of women in all spheres is reflected in the laws and decisions, which give women the opportunity to show their activity in society, in state and non-state organizations.